Brianne Donaldson and Ana Bajželj, Insistent Life: Principles for Bioethics in the Jain Tradition - Chapple, Christopher Key (Journal for the study of religion, nature and culture, 2024)
Brianne Donaldson and Ana Bajželj, Insistent Life: Principles for Bioethics in the Jain Tradition (Oakland: University of California Press, 2021), 294 pp., $34.99 (pbk), ISBN: 9780520380561